Alternative approach for evaluating small ruminant genotypes for meat production in Ethiopia - Ermias, E.; Rege, J.E.O.; Banerjee, A.K. (Langston University, 2000)
Slaughter data from 304 Menz and 153 Horro rams were analysed to determine between breeds differences in yields of carcass and edible non-carcass components, with the primary aim of creating awareness in the way animal evaluations for meat production may be modified to incorporate local cultures. Total edible non-carcass component yield (ENCY) was obtained as the sum of weights of blood, lungs and trachea, liver, heart, kidneys, reticulo-rumen, omaso-abmasum, hindgut, omental and mesenteric fat and kidney fats. Total yield of consumable products (TCPY) was calculated as the sum of hot carcass weight (HCW) and ENCY. Slaughter weight, HCW, ENCY and TCPY were 24.7, 10.5, 4.3, and 14.8 kg, respectively, in the Menz and 24.9, 10.4, 4.6, and 14.9 kg, respectively, in the Horro. Only the breed difference in ENCY was significant (P<0.01). The Menz dressed higher (P<0.01) than the Horro (42 vs 41 percent). This study emphasises the need to pay attention to the total yield of consumable products rather than only to carcass weight and (or) dressing percentage in evaluating the suitability of genotypes for meat production in cultures where non-carcass items are traditionally consumed. Inclusion of this component in breed comparisons may help understand farmer and consumer preferences for certain breeds.